Case reportGraves’ thyrotoxicosis in a patient with metastatic differentiated thyroid carcinoma and chronic lymphocytic leukaemia (CLL) - Makarewicz, Jacek; Mikosiński, Sławomir; Rutkowski, Antoni; Adamczewski, Zbigniew; Lewiński, Andrzej (Archives of Medical Science, 2007)
Thyrotoxicosis is rare in patients with thyroid carcinoma. A case is reported of a 66-year-old woman with Graves’ disease, papillary thyroid carcinoma (PTC) with pulmonary metastases and chronic lymphocytic leukaemia (CLL). After thyroidectomy and antithyroid drug (ATD) withdrawal, thyrotoxicosis recurred. Treatment with ATD and 131I (six doses, 36.3 GBq in total) resulted in permanent hypothyroidism and significant destruction of lung metastases. The course of CLL was mild, but transient anaemia and thrombocytopenia were observed after 131I therapy. Pathomechanisms of thyrotoxicosis in patients with metastatic thyroid carcinoma, its treatment and its relation to CLL are presented.